Protective Roles of Natural IgM Antibodies - Grönwall, Caroline; Vas, Jaya; Silverman, Gregg J. (Frontiers in Immunology, 2012)
Antibodies are a vital part of the armentarium of the adaptive immune system for the fine-tuning of the recognition and response to foreign threats. However, in health there are some types of antibodies that instead recognize self-antigens for the enhancement of primitive innate functions. The repertoire of natural IgM antibodies is postulated to have been selected during immune evolution for their contributions to critical immunoregulatory and housekeeping properties. The clearance of dying cells is one of the most essential responsibilities of the immune system, which is essential to prevent uncontrolled inflammation and autoimmunity. In the murine immune system, natural IgM antibodies that recognize apoptotic cells have been shown to enhance the phagocytic clearance of dead and dying cells and to suppress innate immune signaling pathways. In the mouse, natural IgM are often the products of B-1 cell clones that arise during immune development without an absolute requirement for exogenous antigenic stimulation. In patients with systemic lupus erythemtosus, IgM autoantibodies, which bind to neo-epitopes on apoptotic cells, have been demonstrated to be present at significantly higher levels in patients with lower disease activity and with less severe organ damage. While certain specificities of IgM autoantibodies correlate with protection from lupus renal disease, others may convey protective properties from lupus-associated atherosclerotic cardiovascular disease. New unexpected insights into the functional roles of IgM antibodies are still emerging, especially regarding the functions of natural antibodies. Herein, we review recent progress in our understanding of the potential roles of natural IgM autoantibodies in the regulation of immune homeostasis and for protection from autoimmune and inflammatory diseases.